(3YbhO GdJLGQI GdEdcJQhfjI (B:s (3GdYbhO GdGdcJQhfjI(B-(3GdefGRYGJ GdYbOjI hZjQ GdYbOjI(B-(3GdbGfhf GdhGLH GdJWHjb (B/s - (3CHh GdgjLGA, eMeO EHQGgjes ((3YeGf(B: s (3OGQ GdKbGaI ddfTQ hGdJhRjY(B, s, 2005)
(3THcI GdEfJQfJ,GdJLGQI GdEdcJQhfjI,YbhO GdJLGQI GdEdcJQhfjI hGdPj SfJfGhdg ef NdGd aUdjf,GdYbO GdEdcJQhfj,EKHGJ GdYbO GdEdcJQhfj,bhGYO GdESfGO hYbhO GdJLGQI GdEdcJQhfjI,bhGYO GdESfGO GdJbdjOjI,eOi edGFeI bhGYO GdESfGO ddJWHjb Ydi YbhO GdJLGQI GdEdcJQhfjIs
(3GdedGMb(B:(3U(B.127-158(3;(B159-166(3;GdQSGFd hGdCHMGK(B:(3U(B.167-169(3;eLehYI GdCMcGe hGdbhGfjf(B:(3U(B.170s
Keywords: (3GdJLGQI GdEdcJQhfjIs; (3GdYbhO GdJLGQjIs; (3GdbGfhf GdJLGQjs